2019
DOI: 10.1039/c9na00506d
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of charged anisotropic nanoparticles at oil–water interfaces

Abstract: Oil properties significantly affect the adsorption of charged anisotropic nanoparticles at oil–water interfaces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
57
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(67 citation statements)
references
References 35 publications
10
57
0
Order By: Relevance
“…However, in contrast to the time scale of hours for CNCs adsorption at the A/W interface [31] , the time scale of present lag-phase was only minutes. This indicated that the lower kinetic adsorption barrier for cellulose nanoparticles adsorbed at the O/W interface compared to the A/W interface, probably due to enhanced wetting of cellulose nanoparticles by oil compared to air [33] .
Fig.
…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…However, in contrast to the time scale of hours for CNCs adsorption at the A/W interface [31] , the time scale of present lag-phase was only minutes. This indicated that the lower kinetic adsorption barrier for cellulose nanoparticles adsorbed at the O/W interface compared to the A/W interface, probably due to enhanced wetting of cellulose nanoparticles by oil compared to air [33] .
Fig.
…”
Section: Resultsmentioning
confidence: 98%
“…This decreased lag-phase time indicated earlier adsorption for cellulose nanoparticles at the O/W interface, due to its small particle size and higher hydrophobicity. Moreover, those nanoparticles lowered interfacial tension, resulting in the decrease of the particle adsorption energy [33] . However, the G” was always larger than G’ and no crossover of G’ and G” within the measured time sweep.…”
Section: Resultsmentioning
confidence: 99%
“…A clear correlation between the oil polarity and the adsorption behavior was found. 28,38 Furthermore, it was shown that the oil properties significantly control the interfacial network rheology and formation kinetics of BLG. 29 Herein, we systematically investigate the influence of oil polarity on layer formation and rheological strength of the 2D nanolayers of three different well-studied globular proteins (BLG, BSA, and LSZ) at fluid interfaces.…”
Section: Analysis Of the Protein Configuration In Solution And After mentioning
confidence: 99%
“…The purity of the oil phase was confirmed by measuring the constant oil-water interfacial tension with a droplet profile tensiometer (PAT-1, SINTERFACE Technologies), as described in literature. 28,29,38,45,46 An oil droplet was formed at the tip of an U-shaped capillary tip in 10 mg/L protein solution. The interfacial tension was extracted from the contour of the drop, monitored by a charge-coupled device camera, by axisymmetric drop shape analysis.…”
Section: Dilatational Rheologymentioning
confidence: 99%
See 1 more Smart Citation